Characterization of hydroxyapatite in biomimetic solution: article - Hashim, Amirul Hafizi; Hamzah, Fazlena (2017)
The aim of this study is to synthesis a biomimetic technique that synthesis a bone like-apatite in biomimetic solution and to optimize decomposition of hydroxyapatite (HAp) crystals by modification of ion concentration in simulated body fluid solution. HAp has a wide range of medical application due to its biological apatite condition. However, elevated processing conditions such as higher temperature have been report to produce hydroxyapatite with properties different from biological apatite. To overcome this limitation, the synthesis of hydroxyapatite involves the use of simulated body fluid with controlled parameter to growth hydroxyapatite at body temperature & physiological pH has been explore. The presence study was conducted using precipitation of HAp in biomimetic technique. HAp was synthesis in simulated body fluid with the presence of Ca and P precursor, dried at 80oC and calcined at 800oC for 2hr. The result shows that the hydroxyapatite produced was as B type carbonated HAp with well-formed crystallinity. However, the incubation period of calcination during HAp formation was not enough due to presence of calcium phosphate. This bone-like apatite can be used as material in bone structure and any medical area.